Accretionary and collisional orogenesis in the south domain of the western Central Asian Orogenic Belt (CAOB). (March 2018) - Cai, Keda; Long, Xiaoping; Chen, Huayong; Sun, Min; Xiao, Wenjiao
Abstract: The Central Asian Orogenic Belt (CAOB) was the result of long-lived multi-stage tectonic evolution, including Proterozoic to Paleozoic accretion and collision, Mesozoic intracontinental modification, and Cenozoic rapid deformation and uplift. The accretionary and collisional orogenesis of its early history generated a huge orogenic collage consisting of diverse tectonic units including island arcs, ophiolites, accretionary prisms, seamounts, oceanic plateaus and micro-continents. These incorporated orogenic components preserved valuable detailed information on orogenic process and continental crust growth, which make the CAOB a key region to understanding of continental evolution, mantle-crust interaction and associated mineralization. The western CAOB refers to the west region in North Xinjiang of China and circum-Balkash of Kazakhstan, with occurrences of the spectacular Kazakhstan orocline and its surrounding mountain belts. Because orogenic fabrics of this part mostly preserve their original features caused by the interactions among the southern Siberian active margin in the north and the Tarim Craton in the south, the western CAOB can be regarded as an ideal region to study the processes of the accretionary and collisional orogenesis and associated mineralization. Since a large number of researchers have been working on this region, research advances bloom strikingly in a short-time period. Therefore, we, in this special issue, focus on these new study advances on the south domain of the western CAOB, including the Kazakhstan collage system, Tianshan orogenic belt and Beishan region, and it is anticipated that this issue can draw more attention from the international research groups to be interested in the studies on orogenesis of the CAOB.